From Nursing Information Systems to Patient Information Systems - Coward, P. M. (Methods of Information in Medicine, 1994)
Clinical information systems, developed for specific disciplines, reinforce the fragmentation of patient care and fail to support integrated, patient centered approaches. Fundamental restructuring of systems development is required to prepare the health care system and the practice of nursing for the future.
Keywords: Nursing Informatics; Clinical Information Systems